PENDAPATAN USAHATANI PADI SAWAH DI SUBAK SEMBUNG KELURAHAN PEGUYANGAN KECAMATAN DENPASAR UTARA - Florianus Galgani; I Ketut Arnawa; I Made Sukerta (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2018)
Subak Sembung is an area located in the green area of Peguyangan urban village of Denpasar. One of the agricultural sub-sectors is rice crops because rice includes staple food which is very dominant to survive, so that rice farming is still the mainstay of farmers to fulfill their household needs and community needs. The purpose of this research is to know (1) paddy farming income income in Subak Sembung Kelurahan Peguyangan District of North Denpasar (2) level of efficiency value of paddy field farming in Subak Sembung Kelurahan Peguyangan District of North Denpasar. This research was conducted in Peguyangan Village, North Denpasar District of Denpasar Regency with "Purposive Sampling" method. Respondents were taken by simple random sampling of 50 farmers who worked on rice field farming. The results of this study showed that the average income earned by farmers amounted to Rp 21,110,328 and R / C value of 4.59. This means that every single rupiah spent will receive a revenue of Rp 4.59 at the end of production. So it is very important role in the income of farmers Subak Sembung Kelurahan Peguyangan. Based on the results of research in rice farming is expected to continue to be developed so that increased rice efficiency.